Streetscape Quality in Jalan Jenderal Basuki Rahmat Corridor Malang based on Public Perception - Aigan Fanda; Lisa Dwi Wulandari (Jurnal Mahasiswa Departemen Arsitektur, 2023)
The streetscape refers to the visual aspects of buildings, road surfaces, and natural elements, such as vegetation and buildings. The Kajoetangan Heritage Area in Malang, which has been an office and trade area since the 1800s, has been redesigned to restore its historical value and boost the city's attractiveness. Persepsi publik tentang kualitas visual dan fisik jalan raya adalah tujuan dari penelitian ini. Untuk mendapatkan data, quantitative descriptive approach was used, including field observations, surveys, and questionnaires. Multiple linear regression analysis was used to analyze the data. The results showed that the building facades were the most important streetscape elements for improving the image of the Kajoetangan Heritage Area.